The Role of Several External Factors on Controlling Rabies In The City of Medan - Rasmaliah Rasmaliah; Hiswani Hiswani; Sri Novita Lubis (The Faculty of Veterinary Medicine of Syiah Kuala University, 2019)
Rabies cases are widespread worldwide and mostly prevalence in develeloping countries. Several Province in Indonesia are still categorized as endemic rabies, including the Province of North Sumatera. This research was aimed to evaluate the role of external factors that could influence in reduction the rabies suspected cases in the population of the City of Medan. The survey was conducted using a structured questionnaire. A Case-Control Design was used in this study. The two groups were rabies suspected case and rabies unsuspected case (control), consisted both male and female respondents. All the population involved in this study were living in the City of Medan. Primary and secondary data were collected using purposive sampling approach. Data were analysed by univariate analysis, bivariate analysis, and multivariate analysis. The result was obtained the ratio of 1:2 between rabies suspected case (64 cases) and rabies unsuspected case (128 cases) in the City of Medan. The bivariate analysis showed the significant influence of the role of livestock department officer, role of health worker, role of community leader and vaccination tools on the rabies suspected case (P0.05). Multivariate analysis showed that the dominant variable which affect the rabis suspected case was rabies vaccine tools.